Kritická analýza zřízení evangelické církve v Předlitavsku - Adam Csukás (Právněhistorické studie, 2020)
The paper deals with the legal history of Protestant church, especially with the leading ideas of the Church Constitution of 1861, as well as with the circumstances of the adoption of the Church Constitution of 1866. It pays special attention to the national and confessionalistic efforts of Bohemian and Moravian Protestants, both Reformed and Lutheran, and therefore further deals with the proposal for the establishment of the Bohemian-Moravian Synod and the proposal of the Church Constitution of Čáslav, which in 1917/1918 influenced the merger of the Czech-speaking Bohemian and Moravian Protestant congregations into the Evangelical Church of Czech Brethren.